Options for the Development of Liberia's Energy Sector - World Bank (Washington, DC, 2013)
Liberia suffered successive armed conflicts from 1989 to 2003 that devastated its economy, infrastructure, human capital, and institutions, including those of the energy sector. The Accra peace agreement of August 2003 marked a transition toward national reconciliation and stabilization that allowed the country to hold elections in 2005. The newly elected Government endorsed programs and policies aimed at improving governance, building capacity, and managing post conflict recovery through stabilizing the economy and supporting economic reconstruction. The purpose of this paper is to present stakeholders in the Liberian energy sector-and the Liberian citizen in general-with options that might expand access and modernize energy services. The four pillars of the National Energy Policy (NEP) are: 1) universal energy access, including the development of an energy master plan; 2) least-cost production of energy and protection of the most vulnerable households; 3) the adoption of international best practices in the electricity sector; and 4) the acceleration of public and private partnership in the sector. The electricity demand estimate for Liberia has been based on available data, including that collected during Liberia's 2008 census. The supply options under consideration cover all options that appear technically feasible for Liberia in 2010.